Revisão das espécies brasileiras do gênero Rhammatocerus Saussure, 1861 (Orthoptera, Acrididae, Gomphocerinae, Scyllinini) - Pujol-Luz, Cristiane Vieira de Assis (1997)
At the present, some species of Rhammatocerus Saussure, 1861 are considered as the greatest pest in Brazilian crops and fourteen species has been recognised in this genus (CARBONELL, 1995). Herein, ten species are revised, two new synonymies are proposed and two new species are described: Rhammatocerus viatorius viatorius (Saussure, 1861), Rhammatocerus schistocercoides (Rehn, 1906), Rhammatocerus palustris Carbonell, 1988b, Rhammatocerus pratensis (Bruner, 1904), Rhammatocerus brunneri (Giglio-Tos, 1895) (= Rhammatocerus conspersus (Bruner, 1904) n. syn.), Rhammatocerus pictus (Bruner, 1900), Rhammatocerus brasiliensis (Bruner, 1904), Rhammatocerus suffusus (Rehn, 1906) (= Rhammatocerus smithi (Rehn, 1906) n. syn.), Rhammatocerus guerrai sp.n. and Rhammatocerus pseudocyanipes sp.n. All species revised in this work occur in Brazil except R. viatorius, type-species of the genus. A key for identification of the Brazilian species is given, as well descriptions of spermatecae showed themselves as extremely efficient characters to species identifications and they are used at the first time for the tribe Scylinini. Descriptions are accompanied by illustrations of the head, thorax, hind femora, spermatecae and photographs of the species habitus. Maps of the specific geographical distribution are also furnished.